Surfactant-assisted catalytic aquathermolysis of heavy crude oil using CuO@TiO2 nanocomposite - Asmaa S. Morshedy; M. M. Abdelhamid; Tahany Mahmoud (Journal of Petroleum Exploration and Production Technology)
Abstract Heavy crude oil is very challenging in the petroleum industry, owing to its complicated molecular composition and high viscosity, which make extraction, transportation, and refining difficult. Breaking through these challenges is essential to the efficiency of oil recovery and global energy demands. In this research, CuO@TiO₂ nanocomposites and surfactants in catalytic aquathermolysis are investigated as an efficient method for improving the flow properties and quality of heavy crude oil. Three nanocomposites of CuO@TiO₂ with varying CuO loadings (25%, 50%, and 75%) were synthesized and characterized using advanced techniques such as FT-IR, Raman spectroscopy, SEM, XRD, BET, and TGA. The 50% CuO@TiO₂ nanocomposite possessed the optimum structural and catalytic properties, displaying a superior 72.4% reduction in viscosity of extra-heavy oil at 220 °C. Analytical techniques such as FT-IR, SARA analysis, and viscosity analysis attested to significant decreases in the resin (34.2%) and asphaltene (20.4%) contents, with increases in saturated (29.4%) and aromatic (36.04%) hydrocarbons. Catalytic process involved major reactions such as pyrolysis, hydrogenation, and desulfurization, targeting C–S, C–N, C–O, and C–C bonds. The synergistic effect of the CuO@TiO₂ nanocomposite and surfactants not only facilitated better oil mobility but also improved recovery efficiency, thus providing an eco-friendly and cost-effective approach to heavy oil upgrading. This study is an extension of our earlier study by demonstrating a new catalytic system based on the integration of nanocomposites with surfactants that achieves remarkable enhancement in reducing viscosity and oil quality. The results demonstrate the promise of this method for industrial implementation, allowing for the development of more efficient and environmentally friendly heavy oil recovery technologies. Graphical abstract